Floristic differentiation in limestone outcrops of southern Mexico and Central Brazil: a beta diversity approach - Perez Garcia, E.A.=700 1 Sevilha, A.C.; Meave, J.A.; Scariot, A.
(Es, En)
ilus., 59 ref.
Keywords: BOSQUE TROPICAL; SECO; BIODIVERSIDAD; COMPOSICION BOTANICA; MATORRAL; TAXONOMIA; MEXICO; DIVERSIDAD ALFA; DIVERSIDAD BETA; BOLETIN DE LA SOCIEDAD BOTANICA DE MEXICO